VLSI implementation of 477MHz CMOS ring voltage controlled oscillator - 371029 Eva Azelia Salleh (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) Universiti Teknologi Malaysia, 2006